The dynamics of family harmony in the Javanese weton perspective - Hidayati, Anni Nurul; Idris, Jarir; Marhamah, Uswatun (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The day of birth is considered as a sacred day relating to the marriage concept well-known as weton, and it is a hereditary heritage. Javanese believe that weton influences psychological aspects relating to social life. This study examines weton measurement that is conceived to take an action and a decision, including in the marriage aspect. This study employs qualitative description to elaborate the phenomena. In addition, this study utilizes ethnography to seek the social pattern in Kartasura, Central Java. The result shows that ancient people used weton as a fundamental aspect to decide their heir’s marriage, and the weton is related to philosophical values upholding family harmony. Therefore, weton becomes popular among Javanese to decide every aspect of life, including marriage.